The jury in Boyacá, 1857-1886: Analysis of its contribution to the administration of justice (2019)
Within the framework of current criminal law studies in Colombia, it is necessary to analyze and debate the history of the jury during the second half of the 19th century. The objective of this article is to analyze its contribution to the administration of justice in the State of Boyacá, from the description of its operation, the problems of its implementation and the legal and political speeches of opposition to the figure. A methodology of the descriptive historical type with a qualitative approach is used, based on the analysis of official primary sources, located in the archives of the Department of Boyacá and the National Library of Colombia. Evidencing the role of the law against the design of the jury, its structure, ordination and contribution in the processing of ordinary judicial processes, which required citizen participation in the function of administering justice. Concluding that, being limited, exclusive and excluding, I can not reconcile with the social and cultural reality of the Boyacá population of this period, due to the lack of public spirit and a true understanding of the figure, despite the efforts of the liberals radicals to modernize the administration of justice in the federal context. © Policia Nacional de Colombia. All rights reserved.